Graduates employability: An exploratory Literature Review - Moumen Aniss; Mejjad Nezha (SHS Web of Conferences, 2021)
This paper aims to present an exploratory literature review from the “Education and Training” journal indexed in Scopus, which has published 99 articles about “Graduate Employability” from 2005 to 2021. After cleaning, classifying and reading these articles with NVIVO; As a result, we have found that authors utilize: quantitative, qualitative, mixed and experimental methodology to address problems related to graduate attributes, graduate employability skills and constructs, enhance employability, self-employability perception and employers perceptions. Also, we have identified three famous conceptual frameworks to measure graduate employability: the Graduate Employability Development model [1], the CareerEDGE model [2] and the Career Management Employability model [3].